2016
DOI: 10.4103/2249-4863.192340
|View full text |Cite
|
Sign up to set email alerts
|

A study of risk factors and foot care behavior among diabetics

Abstract: Background:Diabetic foot results in considerable morbidity and mortality in developing countries and the prevalence of diabetes is expected to increase further in the next decades in these countries. Diabetic ulcers are the most common foot injuries leading to lower extremity amputation. Family physicians have a pivotal role in the prevention or early diagnosis of diabetic foot complications. Patient education regarding foot hygiene, nail care and proper footwear is crucial to reducing the risk of an injury th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 14 publications
8
32
2
4
Order By: Relevance
“…8 Some patients with diabetic neuropathy have insensate feet and are thus more prone to injury, are less aware when injuries happen, and are at greater risk of developing foot ulcerations. 23,24 Charcot or diabetic foot syndrome, first described in 1883, is a dreaded complication of DSPN, due to the greatly elevated risk of lower extremity amputation. This syndrome has been defined as the development of foot injuries and ulcerations in association with peripheral neuropathy, peripheral arterial disease, localized trauma, inflammation, and acquisition of infection.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…8 Some patients with diabetic neuropathy have insensate feet and are thus more prone to injury, are less aware when injuries happen, and are at greater risk of developing foot ulcerations. 23,24 Charcot or diabetic foot syndrome, first described in 1883, is a dreaded complication of DSPN, due to the greatly elevated risk of lower extremity amputation. This syndrome has been defined as the development of foot injuries and ulcerations in association with peripheral neuropathy, peripheral arterial disease, localized trauma, inflammation, and acquisition of infection.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…When this term is focused on individuals with DFU, it may put a lot of emphasis on a specific approach such as the DFU nursing process (assessment, interventions and evaluation) and how the individuals and their families interact with their surrounding communities. In line with reasoning, successful actions pertaining to wound care require a comprehensive approach including looking at the whole aspect of patient and family, and not just the wound . Therefore, the conceptualisation of the concept outlined in this study facilitates to recognise attributes, antecedents, consequences and the outcomes of such procedures relating to DFU.…”
Section: Discussion and Implication On The Practicementioning
confidence: 93%
“…In our hospital it may be worse, as the patient to doctor ratio is quite high, which may leave the doctor with little time to spend with each patient. Other studies have shown poor knowledge among diabetics with and without foot ulcers [4] [5] [9].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of foot care knowledge and practice in reducing the incidence of amputations in diabetics have been shown [4] [5] [6]. This is even more important in developing countries such as Nigeria, where poverty abounds and patients seek medical intervention late.…”
Section: Introductionmentioning
confidence: 99%